Atlanto-Occipital Synostosis in a Colombian Population Sample - Duque Parra, J.E.; Barco Ríos, J.; García Aguirre, J.F. (Journal of Morphological Sciences, 2018)
Introduction The Cervico-capital rotation process involves important joints with respect to the neurological field. Among these joints, the atlanto-occipital joint accounts for 40% of the total rotation process and its anatomical changes may affect the joint, i.e when the synostosis of both bones occurs. This anomaly has a reported incidence in the world population of 0.14% to 0.75%. To determine whether this incidence range also corresponds to the Colombian population, atlanto-occipital fusion in Colombian patients was studied.Materials and Methods The presence of atlanto-occipital fusion was assessed in a random sample of 105 skulls of a Colombian population. Morphometric features were evaluated by using a Vernier caliper.Results Out of the total sample two cases of atlanto-occipital fusion were identified. One of them exhibited a bilateral fusion between the anterior arch of the foramen magnum and the lateral masses of the atlas; the other one exhibited a left hemisynostosis that compromises the anterior arch foramen magnum and left lateral mass of atlas. The overall frequency of occurrence was 1.9%.Conclusion A greater incidence of atlanto-occipital fusion was found in contrast to the range of world incidence reported in the literature.
Keywords: occipital bone; atlas; atlanto-occipital; synostosis